Piling work of bridge construction at Kampung Wakaf Bunut Laluan Persekutuan 3, Pasir Puteh, Kelantan / Nur Aini Ab Rhaman - Ab Rhaman, Nur Aini (2016)
I have chosen a company for practical training is JKR Pasir Puteh, Pasir Puteh, Kelantan. Many projects have been made possible by JKR Pasir Puteh. During the practical training I have chosen the title of the piling works which JKR Pasir Puteh perform the work for the bridge in Kampung Wakaf Bunut Laluan Persekutuan 3, Pasir Puteh, Kelantan. The research of the project is to know how the process of piling work for bridge construction. Construction is very important to make sure the deep foundation of the bridge must be in strong and safe use by consumers. Before the process of work, designers and engineers must be involved to determine the appropriate conditions including type piles and how many bars of piles should be used or suitable for bridges to be built in Wakaf Bunut Kampaung Laluan Persekutuan 3, Pasir Puteh, Kelantan.